Plant defense compounds can enhance antagonistic effects against Alternaria brassicicola of seed-associated fungi isolated from wild Brassicaceae - Lerenard, Thomas; Aligon, Sophie; Berruyer, Romain; Poupard, Pascal; Le Corff, Josiane (Frontiers in Plant Science, 2024)
Plant microbiota appear more and more as potential sources of antagonistic microorganisms. However, the seed microbiota associated with wild plant species has rarely been explored. To identify fungal antagonists to the seed-borne pathogen Alternaria brassicicola, seeds were collected in natural populations of three Brassicaceae species, Arabidopsis thaliana, Capsella bursa-pastoris and Draba verna. A large number of fungal strains reduced the growth of A. brassicicola. The most antagonistic strains belonged to Alternaria, Apiospora, Trichoderma and Aspergillus. Seedassociated fungi tolerated host plant defenses and exhibited lower sensitivity compared to A. brassicicola to indolic compounds such as the phytoalexin camalexin and the glucosinolates (GLS)breakdown compound indole-3-carbinol. By contrast, antagonistic strains were as inhibited as A. brassicicola in presence of allyl-isothiocyanates (ITC) derived from aliphatic GLS, and more inhibited by benzyl-ITC derived from aromatic GLS. However, all defense compounds could enhance the antagonistic effects of some of the isolated strains on A. brassicicola. The observed potential synergistic effects between defense compounds and seed-associated antagonistic strains emphasize the need for further studies to elucidate the molecular bases of the interactions. A better understanding of the interactions between host plants, pathogens and fungal endophytes is also needed to develop sustainable biocontrol strategies.